2007
DOI: 10.1111/j.1475-6765.2007.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

The frog pond beauty contest: Physical attractiveness and electoral success of the constituency candidates at the North Rhine‐Westphalia state election of 2005

Abstract: Abstract.  Voters usually do not know much about the biography and political agenda of the local candidates for parliament in their constituency. Since posters with photographs of these candidates are omnipresent on the streets during the election campaign, many voters are at least familiar with their facial appearance. As a consequence, the attractiveness of the constituency candidates substantially influences voter behaviour. This is shown by the example of the North Rhine‐Westphalia state election of 2005. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
2
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 44 publications
10
108
2
11
Order By: Relevance
“…While our study is the first study to connect rapidly-determined perceptions of candidate traits to general electoral outcomes in Great Britain, our findings are consistent with a growing literature documenting a relationship between perceptions of candidate traits and voting behaviour in candidate-centric systems such as Brazil (Lawson et al, 2010), Finland (Berggren, Jordahl, and Poutvaara 2010), Ireland (Buckleye et al, 2007), and the United States (e.g., Todorov et al 2005;Benjamin and Shapiro, 2009;Hayes, 2010), as well as an increasing number of more party-centred systems, including Australia (King and Leigh, 2009), Canada (Efron and Patterson, 1974), France (Antonakis and Dalgas, 2009), Germany (Rosar et al, 2008), Great Britain (e.g., Shephard, 2007, 2011;Banducci et al, 2008), and Switzerland (Lutz, 2009). …”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…While our study is the first study to connect rapidly-determined perceptions of candidate traits to general electoral outcomes in Great Britain, our findings are consistent with a growing literature documenting a relationship between perceptions of candidate traits and voting behaviour in candidate-centric systems such as Brazil (Lawson et al, 2010), Finland (Berggren, Jordahl, and Poutvaara 2010), Ireland (Buckleye et al, 2007), and the United States (e.g., Todorov et al 2005;Benjamin and Shapiro, 2009;Hayes, 2010), as well as an increasing number of more party-centred systems, including Australia (King and Leigh, 2009), Canada (Efron and Patterson, 1974), France (Antonakis and Dalgas, 2009), Germany (Rosar et al, 2008), Great Britain (e.g., Shephard, 2007, 2011;Banducci et al, 2008), and Switzerland (Lutz, 2009). …”
Section: Introductionsupporting
confidence: 88%
“…We limit our analyses to two traits that play a prominent role in the literature to date: attractiveness and competence. Perceptions of physical attractiveness have been shown to increase electoral success cross-nationally (e.g., Sigelman et al, 1987;King and Leigh, 2007;Rosar et al, 2008;Lutz, 2010). 9 These findings coincide with those from social psychologists, which indicate that physically attractive individuals tend to be evaluated more positively and are more successful professionally (Marlowe et al 1996;Haas and Gregory 2005).…”
mentioning
confidence: 78%
“…As an example of how information is gained via visual cues, Princeton undergraduate and graduate students were asked to rate photos of American political candidates; it was found that inferences of competence from photos correctly predicted the outcomes of 72% of Senate races and 67% of House of Representatives races [4]. Candidate photos were also used to predict electoral outcomes in general elections in Germany, with more beautiful candidates winning more votes [5]. Another study showed that attractive candidates are more likely to be elected to non-partisan community partnership boards in the UK.…”
Section: Discussion Of Pros and Consmentioning
confidence: 99%
“…For instance, attractiveness increases the candidate's number of votes and thereby the likelihood of being elected (Berggren, Jordahl, and Poutvaara (2010) and Rosar, Klein, and Beckers (2008)). Antonakis and Dalgas (2009) suggest that underlying the effect of physical attractiveness is the voters' belief that attractive candidates are more competent.…”
Section: Literaturementioning
confidence: 99%